Inverse blood pressure rhythm of transgenic hypertensive TGR(mREN2)27 rats: role of norepinephrine and expression of tyrosine‐hydroxylase and reuptake1‐transporter - Lemmer, Björn; Schiffer, Sabine; Witte, Klaus; Gorbey, Stefan (Chronobiology international, 2005)
Transgenic hypertensive TGR(mREN2)27 rats (TGR) exhibit an inverse circadian blood pressure profile from the age of 8 to 9 wk. To investigate the role of the sympathetic nervous system in this pathological blood pressure rhythm, we examined postnatal changes in catecholamine concentration, expression of tyrosine‐hydroxylase (TH), and norepinephrine (NE) reuptake1‐transporter (NET) in the heart, adrenal glands, and hypothalamus of non‐hypertensive TGR at an age of 4 wk and of hypertensive TGR at an age of 10 wk and compared these to normotensive, age‐matched Sprague‐Dawley rats. Rats were kept under synchronized light:dark (LD) conditions of 12:12 h. Blood pressure and heart rate were monitored by radiotelemetry, catecholamines by high performance liquid chromatography, expression of TH and NET (mRNA) by RT‐PCR, and TH protein by Western blots. In normotensive 4 wk‐old Sprague‐Dawley rats, cardiac NE concentrations were circadian phase‐dependent with lower values at ZT12.5, with no differences observed, in 10‐wk‐old animals. At both ages however, sympathetic tone was higher during the dark phase, as shown by a higher turnover of NE. This observation confirms earlier data, which indicate that the endogenous amine concentration may not mirror its turnover rate. TGR at either age had lower cardiac NE as well as lower TH expression and did not display a circadian phase‐dependency. The increased cardiac NE turnover rate in the dark phase in non‐hypertensive TGR was lost in hypertensive rats. Both cardiac NE concentrations and TH expression decreased with age in both strains. In adrenal glands, NE and epinephrine (E) were not circadian phase‐dependent in both strains but increased with age. NE concentrations in the hypothalamus were neither circadian phase‐dependent nor different in both strains and at both ages. However, sympathetic tone of NE in the hypothalamus, as indicated by the turnover rate, was greater during the dark phase in both strains at an age of 10 wk. Expression of TH and NET were greatly reduced in adrenal glands when compared to Sprague‐Dawley rats; whereas, expression of TH in the hypothalamus was significantly increased in hypertensive TGR. These data indicate that the transgene in TGR leads to an increased central stimulation of the sympathetic nervous system and to a consecutive down‐regulation in the peripheral organs. It is of interest that rhythmicity in the studied parameters was lost in hypertensive TGR, except in the turnover of NE in the hypothalamus. We concluded that the data on key mechanisms of regulation of the sympathetic system in TGR cannot explain the inverse blood pressure rhythm observed in this transgenic rat strain.